2021
DOI: 10.21608/ejhc.2021.176818
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pregnant Women knowledge and attitude towards Umbilical Cord Banking and Stem Cell.

Abstract: Background: Nowadays, the collection of stem cells from the blood of the umbilical cord is one of the most important topics of health sciences and new technology. However, cord blood is now considered a rich source of adult stem cells that can be used to treat many conditions and diseases. It is still a controversial topic. The current study aims to assess pregnant women's knowledge and attitude toward umbilical cord banking and stem cell. Research design: Descriptive exploratory research design was adopted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…While, the other half have negative attitude score (Figure 5). This result is agreement with Reda et al (2021) (25) who found that 67% of their participant had negative attitude and 33% of them had positive attitude. Again, Key Value Pair (2018) (32) who studied pregnant women knowledge and attitude about the storage of cord blood and reported also a negative attitude toward the stem cell and blood banking among the majority of the sample.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…While, the other half have negative attitude score (Figure 5). This result is agreement with Reda et al (2021) (25) who found that 67% of their participant had negative attitude and 33% of them had positive attitude. Again, Key Value Pair (2018) (32) who studied pregnant women knowledge and attitude about the storage of cord blood and reported also a negative attitude toward the stem cell and blood banking among the majority of the sample.…”
Section: Resultssupporting
confidence: 93%
“…This may be due to that more than half of the studied sample did not completes their university education and about one third of them their pregnancy was the first and have not knowledge and experience. This is also may be due to that only 11.6% of studied (25) who revealed that above half of the studied participants had poor knowledge level, less than quarter of them had a good knowledge level toward umbilical cord banking and stem cell. These results were supported also by Habib et al, (2017) (26) who study " knowledge and attitude of Saudi women toward UCB' and revealed that half of the sample had poor knowledge level and only 18% had good knowledge level.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…This study also demonstrated that only 16% of the women in this sample were willing to donate umbilical cord blood, which increased to 91% after an educational intervention. A study from Egypt based on a convenient sample of 200 women showed that over one-third of women had average knowledge about donating UCBCs, and over two-thirds of women had negative attitudes towards this practice [22]. A quantitative study assessed the levels and nature of awareness about cord blood banking by surveying over 1100 participants from the general population in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%